PERCEPTION OF RELIGION AND RELIGIOUS LIFE IN THE PRISON - Tecim, Erhan (Selcuk Univ, Fac Letters, 2009)
It is clear that the people who are prisoners have been isolated from society. in this study, it has been aimed to scrutinize religious way of living that has a social function and value, at what level and how the perception of prisoners about religion, due to this isolation, occurs in the prison environment. ln the scope of the research, based on this research, it has been handled in the correlation between religious life and religious perception with demographical variable. The terms of 'erime' and 'punishment' were mentioned shortly. Also, it was examined that whether being more religiousness or not in the prison. it was determined with the examples taken from American and European countries. Within this study, it has been surveyed of 234 prisoners at Konya E Type Prison and Konya Half-Open Prison. Although some researchers have findings that prisoners getting religiousness in the prison, it has been emerged from different situation in this context. Among the findings is that religiousness has increased when it is evaluated in terms of belief and decreased in terms of practice.
Keywords: Sociology of Religion; criminology; prison; crime; prisoner and religiousness